Pengaruh Jenis Kemasan Dan Lama Penyimpanan Terhadap Karakteristik Mutu Bunga Telang (Cloria Ternatea) Kering - Hotman Manurung; Benika Naibaho; Topma Boang Manalu; NDM Romauli (Rona Teknik Pertanian, 2023)
Abstract The increasing variety of benefits of the butterfly pea flower requires the availability of dried butterfly pea flowers to replace fresh butterfly pea flowers. A study has been carried out on "The Influence of Packaging Type and Storage Time on the Quality Characteristics of Dried Butterfly Pea Flower (clitoria ternatea). The aim of the study was to determine the effect of the type of packaging and storage time on the quality characteristics of dried butterfly pea flowers. The study was conducted using an experimental method with a Completely Randomized Factorial Design (RALF). Treatment of packaging types: K1 = PolyPropylene (PP) Plastic Packaging and K2 = Aluminum Foil (AF) Packaging. Storage time: L0= 0 days; L1= 7 days; L2= 14 days; L3=21 days. The research was conducted with 3 replications. Data were analyzed using SPSS software version 20. Significantly different effects were tested by Duncan's test at the level of p=0.05. The results showed that the water content of the butterfly pea flower was 10.1% in the PP packaging and 9.7% in the AF packaging. Dried butterfly pea flowers contained a total phenol of 9.74 mg/g in PP packaging and 11.5 mg/g in aluminum foil packaging. IC50 values in PP and AF packaging were 242.7 and 224.4 ppm, respectively. The water content of the butterfly pea flowers increased significantly from 8.7% at 0 days of storage to 11.1% at 21 days of storage. Anthocyanin and flavonoid bioactive compounds were detected by positive tests up to 21 days of storage. The total phenol of the butterfly pea flower decreased significantly from 14.95 mg/g at 0 days of storage to 6.19 mg/g at 21 days of storage. IC50 value (antioxidant activity) increased from 140.1 ppm to 293.1 ppm during storage.Keywords: Butterfly pea flower, PolyPropylene and aluminium foil packaging, anthocyanin and phenol  AbstrakMeningkatnya ragam manfaat bunga telang menuntut tersedia bunga telang kering untuk menggantikan bunga telang segar. Telah dilakukan penelitian “Pengaruh Jenis Kemasan dan Lama Penyimpanan Terhadap Karakteristik Mutu Bunga Telang (clitoria ternatea) Kering”. Tujuan penelitian untuk mengetahui pengaruh jenis kemasan dan lama penyimpanan terhadap karakteristik mutu bunga telang kering. Penelitian dilakukan dengan metode ekperimental dengan Rancangan Acak Lengkap Faktorial (RALF). Perlakuan jenis kemasan :  K1 = Kemasan Plastik PolyPropilen (PP) dan K2 = Kemasan Aluminium Foil (AF).  Lama penyimpanan :  L0= 0 hari ; L1= 7 hari; L2= 14 hari ; L3=21 hari. Penelitian dilakukan dengan 3 ulangan. Data dianalisis  menggunakan software SPSS versi 20. Pengaruh yang berbeda nyata diuji dengan uji Duncan pada taraf p=0.05.  Hasil penelitian menujukkan kadar air bunga telang 10,1% pada kemasan PP dan 9,7% pada kemasan AF. Bunga telang kering mengandung total fenol 9,74 mg/g pada kemasan PP dan 11,5 mg/g pada kemasan aluminium foil.  Nilai IC50 dalam kemasan PP dan AF masing-masing 242,7 dan 224,4 ppm. Kadar air bunga telang meningkat secara nyata dari 8,7%pada penyimpanan 0 hari menjadi 11,1% pada penyimpanan 21 hari. Senyawa bioaktif antosianin dan flavonoid terdeteksi uji positif sampai pada penyimpanan 21 hari. Total fenol bunga telang menurun secara nyata dari 14,95 mg/g pada penyimpanan 0 hari menjadi 6,19 mg/g pada penyimpanan 21 hari. Nilai IC50 (aktivitas antioksidan) meningkat dari 140,1ppm sampai 293,1ppm selama penyimpanan.